2023
DOI: 10.1038/s41430-023-01264-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of muscle mass in the immediate post-operative period is associated with inadequate dietary protein and energy intake

Abstract: Despite the implementation of ‘Enhanced Recovery After Surgery’ (ERAS) protocols, major abdominal surgery is still associated with significant and detrimental losses of muscle mass and function in the post-operative period. Although ERAS protocols advocate both early mobility and dietary intake, dietary composition in the immediate post-operative period is poorly characterised, despite muscle losses being greatest in this period. Herein, we show in 15 patients (66 ± 6 y, 12:3 M:F) who lost ~10% m. vastus later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…With inactivity (or SKM disuse) a common experience in hospitalised patients, when this is combined with inadequate nutrition the resultant SKM atrophy is both significant and clinically relevant [ 44 ]. A recent observational study by Hardy et al, in an older post-surgical (for colorectal cancer resection) cohort reported in-hospital nutritional intake in the 5 days after surgery as only ∼25% of ESPEN guidelines for energy and only ∼12% for protein [ 51 ]. Comparing young with older adults, it has been shown that in response to SKM disuse older adults lose SKM mass at a markedly faster rate (∼3–6 times) [ 52 ].…”
Section: Muscle Mass and Ageingmentioning
confidence: 99%
“…With inactivity (or SKM disuse) a common experience in hospitalised patients, when this is combined with inadequate nutrition the resultant SKM atrophy is both significant and clinically relevant [ 44 ]. A recent observational study by Hardy et al, in an older post-surgical (for colorectal cancer resection) cohort reported in-hospital nutritional intake in the 5 days after surgery as only ∼25% of ESPEN guidelines for energy and only ∼12% for protein [ 51 ]. Comparing young with older adults, it has been shown that in response to SKM disuse older adults lose SKM mass at a markedly faster rate (∼3–6 times) [ 52 ].…”
Section: Muscle Mass and Ageingmentioning
confidence: 99%